Formation and properties of NbC-reinforced layers obtained by electroslag surfacing in a small-diameter current-fed crystallizer - Saichuk, Oleksandr; Borovyk, Olena; Borovyk, Vadym; Zakharov, Andrii; Kapustianskyi, Mykola (Technology audit and production reserves, 2025)
The object of research is the process of forming NbC-reinforced composite layers by electroslag surfacing (ESS) in a small-diameter current-fed crystallizer (CFC). The problem being solved is the stable introduction of finely dispersed NbC into a small-diameter slag bath without dissolution and agglomeration, achieving uniform reinforcement, low porosity and high wear resistance. The research is aimed at experimentally determining the microstructure, phase composition, hardness, porosity, and abrasive wear resistance of layers formed under controlled ESS conditions using powder wire containing 35 wt.% NbC, and justifying the technological feasibility of the process in small-diameter CFC. The process was implemented in two-section CFC Ø 65–85 mm under the following conditions: I = 1.1 kA; U = 22 V; feed rate Vsupply = 2.0 m · min⁻¹; melting duration 45 s; Tbath = 1600–1700°C. Morphology and chemical homogeneity were determined by optical microscopy and SEM-EDS; phase composition – by X-ray diffraction; hardness – by Vickers HV10; abrasive wear resistance – according to ASTM G99. Layers of 2.0 ± 0.2 mm without macro-cracks and slag inclusions were obtained, with a uniform distribution of NbC (≈ 2–5 μm) throughout the thickness. The average hardness is 1020 ± 30 HV10 (≈ ×3 compared to steel 20), the linear wear rate is reduced by 3.4 times, porosity is ≤ 0.8 vol.% while maintaining high adhesive strength. It has been confirmed that the controlled feeding of non-current-carrying powder wire into the most heated zone of the bath ensures reproducible transfer of the refractory phase and prevents its dissolution and coarsening. The agreed microstructural features correlate with an increase in hardness and a decrease in wear, confirming the cause-and-effect relationship “structure → properties”. The proposed technology can be implemented on existing ESS installations without re-equipment and is recommended for the restoration of parts operating under conditions of abrasive wear, with the potential for scaling up by regulating modes and controlling slag composition.